Pengaruh Model Pembelajaran Kooperatif Tipe Group Investigation Terhadap Keaktifan Belajar Pendidikan Agama Kristen Siswa Kelas IX SMP Negeri 4 Tarutung Kabupaten Tapanuli Utara Tahun Pembelajaran 2023/2024 - Perawati Siregar; Adiani Hulu; Oloria Malau; Eben H. Telaumbanua; Andrianus Nababan (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
The aim of this research is to determine the positive and significant influence of the Group Investigation Type Cooperative Learning Model on the active learning of Christian Religious Education of class IX students of SMP Negeri 4 Tarutung, North Tapanuli Regency for the 2023/2024 academic year. The research method used is a descriptive quantitative research method, with inferential statistical data analysis. The population is all class IX students at SMP Negeri 4 Tarutung, North Tapanuli Regency for the 2023/2024 Academic Year who are Christians totaling 103 people and a sample of 52 people was determined, namely 50% of the total population using random sampling techniques. Data was collected using a positive closed questionnaire with 44 items, namely 28 items for variable X and 16 items for variable Y which were compiled by the author based on variable indicators according to expert theory. The results of data analysis show that there is a positive and significant influence of the Cooperative Learning Model of the Group Investigation type on the active learning of Christian Religious Education of Class IX students of SMP Negeri 4 Tarutung, North Tapanuli Regency for the 2023/2024 academic year: 1) Test the analysis requirements: a) test a positive relationship The value obtained is rxy = 0.552 > rtable(a=0.05,n=52) = 0.297, thus there is a positive relationship between variable .05,dk=n-2=50)= 2,000, thus there is a significant relationship between variable .35X. b) Regression coefficient of determination test (r2) = 30.4%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(a=0.05, dk numerator k=24, dk denominator=n-2=52-2=50) namely 21.72 > 1.39. Thus Ha is accepted and H0 is rejected.